Arrhythmia‐specific settings for automated high‐density mapping: A multicenter experience. (19th June 2018) - Sommer, Philipp; Albenque, Jean‐Paul; van Driel, Vincent; Pierre, Bertrand; Tondo, Claudio; Roithinger, Franz Xaver; Poty, Hervé; Miller, Amber; Della Bella, Paolo
Abstract: Background: Advancements in electrophysiology 3‐D mapping systems facilitate the broadening scope of electrophysiology study and catheter ablation to treat complex arrhythmias. While electroanatomical mapping systems have default settings available for a variety of mapping parameters, significant operator customization driven by arrhythmia type and experience can occur. However, multicenter comprehensive reporting of customized mapping settings is lacking. Methods: In this prospective, multicenter observational registry, subjects with cardiac arrhythmias underwent electrophysiology study and ablation procedure using the EnSite Precision™ electroanatomical mapping system per standard of care, and associated automated mapping thresholds and procedural characteristics were observed. Results: Cardiac mapping and ablation was performed in 503 patients (64.4% male, 59.6 ± 13.2 years) for a variety of indications including atrial fibrillation (N = 277), atrial flutter (N = 67), other supraventricular tachycardias (N = 96), and ventricular tachycardia (N = 56). Automated electroanatomical mapping was used to generate 88.2% of all maps, and arrhythmia‐specific adjustments of mapping thresholds were utilized to collect electrophysiologically relevant data. The most commonly used thresholds for mapping in AF were Distance (average 2.7 ± 3.5 mm) and Signal‐to‐Noise Ratio (5.2 ± 1.1), while mapping in VT commonly used Score (88.5 ± 6.5%) and Distance (0.6 ± 0.5 mm). Automated mapping collected and utilized 8.8 times more data than manual mapping without increasing mapping time. Conclusions: This registry revealed arrhythmia‐specific automated mapping settings used to generate electroanatomical maps of multiple cardiac rhythms with higher point density than manual mapping without increasing mapping time. Commonly used mapping threshold settings could serve as an important reference for new automated electroanatomical mapping users or those expanding their usage to new indications and arrhythmias.